2010
DOI: 10.1017/s1368980010000339
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the relevance of neighbourhood characteristics to the household food security of low-income Toronto families

Abstract: Objective: Although the sociodemographic characteristics of food-insecure households have been well documented, there has been little examination of neighbourhood characteristics in relation to this problem. In the present study we examined the association between household food security and neighbourhood features including geographic food access and perceived neighbourhood social capital. Design: Cross-sectional survey and mapping of discount supermarkets and community food programmes. Setting: Twelve high-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
99
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(110 citation statements)
references
References 40 publications
9
99
0
2
Order By: Relevance
“…A study employing survey and mapping data in a low-income population of residents of Toronto, Canada, found that proximity to a local food outlet did not reduce the risk of household food insecurity and there was no association between a respondent's perception of adequate food access and the respondent's food security status. 23 Our study's contrasting findings may be attributable to differences between Philadelphia and Toronto, and between Canadian and US food prices and social policies affecting low-income families. One potential explanation for the relationship between access and food insecurity we found is that lack of neighborhood food access increases the costs of food shopping requiring funds and time for transportation, thereby increasing the risk of food insecurity.…”
Section: Discussionmentioning
confidence: 57%
“…A study employing survey and mapping data in a low-income population of residents of Toronto, Canada, found that proximity to a local food outlet did not reduce the risk of household food insecurity and there was no association between a respondent's perception of adequate food access and the respondent's food security status. 23 Our study's contrasting findings may be attributable to differences between Philadelphia and Toronto, and between Canadian and US food prices and social policies affecting low-income families. One potential explanation for the relationship between access and food insecurity we found is that lack of neighborhood food access increases the costs of food shopping requiring funds and time for transportation, thereby increasing the risk of food insecurity.…”
Section: Discussionmentioning
confidence: 57%
“…In terms of characteristics of the target populations studied, seven of the eighteen studies examined adults of varying ages (37)(38)(39)(43)(44)(45)(46) , seven explicitly examined families with children (sometimes with data collected using the child as the sampling unit) (40,42,(47)(48)(49)(50)(51) , three focused on seniors (41,52,53) , and one sampled a range of ages (children and adults) (54) . Seven out of the eighteen studies (39 %) focused exclusively on low-income or ethnic subgroups (39,44,46,(48)(49)(50)(51) .…”
Section: Literature Search and General Overviewmentioning
confidence: 99%
“…Seven out of the eighteen studies (39 %) focused exclusively on low-income or ethnic subgroups (39,44,46,(48)(49)(50)(51) .…”
Section: Literature Search and General Overviewmentioning
confidence: 99%
See 2 more Smart Citations